The Urgency of Transformation Digital in Education Institution - Saprudin, Saprudin; Wujarso, Riyanto; Andhitiyara, Revan (Jurnal STEI Ekonomi, 2023)
Education in the 4.0 revolution era demands the agility and adaptability of the resources involved in the education sector, especially educational institutions, to the digital revolution, especially with the rise of Information and Communication Technology (ICT). Therefore, this study aims to discuss digital transformation in the field of education and the importance of digital transformation in educational institutions. This study uses a qualitative approach with descriptive methods with literature review as a source of data without going to the field. Data collection techniques by collecting important information related to research and then analyzing data by reducing data, displaying data and drawing conclusions. The results of the study show that digital transformation is very influential in the world of education, especially in educational institutions, because digital transformation makes learning activities easy and flexible in implementation. Important things for digital transformation in educational institutions include changing conventional systems to digital, providing applications that can be accessed by anyone at any time, and providing experts who are competent in their fields. This research concludes that in realizing digital transformation, educational institutions can pay attention to digital infrastructure and global vision and create a national digital learning system. The implication of this research is that it is important for educational institutions to improve technology infrastructure and provide training for teachers and educational staff in digital literacy. In addition, education must have a global perspective and build an integrated national digital learning system. This research has limitations, namely the lack of data and limited time to explore the impact of digital transformation as a whole.